Private Higher Education in Pakistan - Halai, Nelofer (International Higher Education, 2011)
Private higher education though a relatively recent development in Pakistan has shown very rapid growth. From the year 1983 when the first private university was established there are now more than sixty universities and degree awarding institutions in Pakistan in the private sector. Similar to the trend in other developing countries these institutions, with few exceptions, are of poor quality. While they do play a role in enhancing access to a larger number of students but the government will have to play a stronger role in ensuring that quality standards are met. Private schools set up by philanthropic trusts can be used as a model for development of tertiary institutions.